Chemical compositions and characterisation of skin gelatin from farmed giant catfish (Pangasianodon gigas) - Jongjareonrak,A. (Academic Press Inc., 2015)
Gelatin was extracted from the skin of farmed giant catfish (Pangasianodon gigas) with a yield of 20.1 g/100 g skin sample on the basis of wet weight. The chemical composition and properties of gelatin were characterised. The gelatin had high protein (89.1 g/100 g) but low fat (0.75 g/100 g) content and contained a high number of imino acids (proline and hydroxyproline) (211 residues per 1000 residues). Giant catfish skin gelatin had a slightly different amino acid composition than calf skin gelatin. The bloom strength of the gelatin gel from giant catfish skin gelatin (153 g) was greater than that of calf skin gelatin (135 g) (P < 0.05). Viscosity, foam capacity and foam stability of gelatin from giant catfish skins were in general greater than those of the gelatin from calf skin tested. SDS-PAGE of giant catfish skin gelatin showed a high band intensity for the major protein components, especially, α-, β- and γ-components and was similar to that of standard calf skin collagen type I. © 2009 Elsevier Ltd. All rights reserved.